Gallic Acid Prevents the Oxidative and Endoplasmic Reticulum Stresses in the Hippocampus of Adult-Onset Hypothyroid Rats - Blas-Valdivia, Vanessa; Franco-Colín, Margarita; Rojas-Franco, Placido; Chao-Vazquez, Alberto; Cano-Europa, Edgar (Frontiers in Pharmacology, 2021)
Thyroid hormone is essential for hippocampal redox environment and neuronal viability in adulthood, where its deficiency causes hypothyroidism related to oxidative and endoplasmic reticulum stresses in the hippocampus, resulting in neuronal death. One option of treatment is antioxidants; however, they must be transported across the blood-brain barrier. Gallic acid is a polyphenol that meets these criteria. Thus, this study aimed to prove that the neuroprotective mechanism of GA is associated with the prevention of oxidative and endoplasmic reticulum stresses in the hippocampus of adult-onset hypothyroid rats Male Wistar rats were divided into euthyroid (n=20) and hypothyroid groups (n=20). Thyroidectomy with parathyroid gland reimplementation caused hypothyroidism. Each group was subdivided into two: vehicle and 50 mg/Kg/d of gallic acid. Three weeks after thyroidectomy, six animals of each group were euthanized, and the hippocampus was dissected to evaluate oxidative and endoplasmic reticulum stress markers. The rest of the animals were euthanized after four weeks of treatment for histological analysis of the hippocampus. The results showed that hypothyroidism increased lipid peroxidation, reactive oxygen species, and nitrites; it also increased endoplasmic reticulum stress by activating the inositol-requiring enzyme-1 (IRE1) pathway, the protein kinase RNA-like endoplasmic reticulum kinase (PERK) and activated transcription factor 6 (ATF6 pathways associated with a proapoptotic state that culminates in hippocampal neuronal damage. Meanwhile, the hypothyroid rat treated with gallic acid reduced oxidative stress and increased endoplasmic reticulum-associated degradation (ERAD) through IRE1 and ATF6. Also, the gallic acid treatment prevented the Bax/BCl2 ratio from increasing and the overexpression of p53 and caspase 12. This treatment in hypothyroid animals was associated with the neuronal protection observed in the hippocampus. In conclusion, gallic acid prevents hypothyroidism-induced hippocampal damage associated with oxidative and endoplasmic reticulum stresses.